Depression and stressful environments: identifying gaps in conceptualization and measurement. Issue 4 (3rd July 2016) - Hammen, Constance
ABSTRACT: Background and Objectives : Stress is well known as a trigger of depressive reactions, fear, anxiety, and behavioral disorders. However, there are many gaps in the conceptualization and measurement of environmental stress.Results : Exciting developments in the neuroscience of stress have increasingly expanded our knowledge of mechanisms by which stress may affect emotional and behavioral adjustment. Ironically, environmental stress has often been a silent player in human studies of stress processes. There is a significant need for increased efforts to include environmental stress variables in models of internalizing and other disorders. Measurement and conceptualization issues are prominent, and this article makes the case for improved methods of measuring acute, chronic, and early life stress, and for additional conceptualization of the dynamically changing and bidirectional effects of stress on disorder over time.Conclusions : There is a critical need for greater focus on and better measurement of the environment and its impact on emotional and other disorders, with emphasis on developmentally informed hypotheses. Empirical findings and new perspectives may contribute enormously to our understanding of normal and abnormal outcomes, and also to the challenge of effective interventions to promote mental health and optimal functioning.